Does External Work Locus of Control Enhance the Exposure to Workplace Bullying? Moderator Role of Social Support - Seckin Halac, Duygu; Minibas-Poussard, Jale; Seçkin-Çelik, Tutku (International Journal of Contemporary Economics and Administrative Sciences, 2022)
Workplace bullying in higher education is under researched, although academics are increasingly reported as a suffering group. Based on the explanation power of the interaction between people and the environment in the psychological field, this paper analyzes the moderation effect of social support in the relationship between external work locus of control (E-WLOC) and workplace bullying in Turkey’s higher education context. Data were collected through questionnaires. It is found that people with an E-WLOC are more exposed to bullying if they get less social support.